Probing subunit-subunit interactions in the yeast vacuolar ATPase by peptide arrays. - Lee S Parsons (PLoS ONE, 2012)
BACKGROUND:Vacuolar (H(+))-ATPase (V-ATPase; V(1)V(o)-ATPase) is a large multisubunit enzyme complex found in the endomembrane system of all eukaryotic cells where its proton pumping action serves to acidify subcellular organelles. In the plasma membrane of certain specialized tissues, V-ATPase functions to pump protons from the cytoplasm into the extracellular space. The activity of the V-ATPase is regulated by a reversible dissociation mechanism that involves breaking and re-forming of protein-protein interactions in the V(1)-ATPase - V(o)-proton channel interface. The mechanism responsible for regulated V-ATPase dissociation is poorly understood, largely due to a lack of detailed knowledge of the molecular interactions that are responsible for the structural and functional link between the soluble ATPase and membrane bound proton channel domains. METHODOLOGY/PRINCIPAL FINDINGS:To gain insight into where some of the stator subunits of the V-ATPase associate with each other, we have developed peptide arrays from the primary sequences of V-ATPase subunits. By probing the peptide arrays with individually expressed V-ATPase subunits, we have identified several key interactions involving stator subunits E, G, C, H and the N-terminal domain of the membrane bound a subunit. CONCLUSIONS:The subunit-peptide interactions identified from the peptide arrays complement low resolution structural models of the eukaryotic vacuolar ATPase obtained from transmission electron microscopy. The subunit-subunit interaction data are discussed in context of our current model of reversible enzyme dissociation.